(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
In this work we discuss the extracurricular activities on physics education. Purpose of extracurricular activities is to help ensure that students achieve the planned results of mastering the main educational program (personal, meta-subject, subject) of primary general education. The organization of extracurricular activities within the social direction can be based on socially useful activities.